MENGENAL KEADAAN ALAM, KEADAAN SOSIAL, DAN KEBUDAYAAN MASYARAKAT ARAB SEBELUM ISLAM DI BUKU SKI DI MI - Abdul Gani Jamora Nasution; Alfiah Khairani; Alliyah Putri; Muliana Fitri Lingga; Salsabila Saragih (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2023)
Arab society before Islam was a society that lived in the Jahiliyah era. Jahiliyyah which means ignorance and in Islamic law Jahiliyyah means "ignorance of divine guidance" or "condition of ignorance of God's guidance". This paper aims to get to know the natural conditions, social conditions and culture of Arab society before Islam. The results of the study: The Arabian Peninsula is a desert region located in the southwestern part of Asia. The Arabian Peninsula was a strategic area on ancient world maps, when the Australian and American continents were unknown to people, because it was located at the meeting point of three continents, namely Asia, Europe and Africa. The northern region challenges Arabia with the Syrian desert valley, the east is bordered by the Persian plateau, while the west is bordered by the Red Sea. The Arab region consists of deserts where the air is very hot and windy, this area is the Tihamah area, while the area that is in the form of valleys in the mountains is the Hijaz area. The social condition of Pre-Islamic Arab society was based on ethnicities that continued to maintain the teachings of their ancestors, by continuing to maintain traditions such as humiliation, killing female babies, worshiping idols, gambling, stealing, drinking intoxicants, robbing and justifying any means to make wishes come true. The most prominent pre-Islamic Arab cultural community is the field of Arabic literature, especially Arabic poetry. The country of Yemen is a very important cultural growth place that once developed in the Arabian Peninsula before Islam came. The Arab nation is a nation that has a high sense of art.